A clinical study of maternal outcome in post dated pregnancy in a tertiary care hospital - Anand, Nikhil; Shah, Hardik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy lasting beyond 40 weeks is a known complication of normal delivery. Studies have found incidence between 2-14%. Post-dated pregnancy carries specific hazards to both mother and fetus. While mothers are faced with problems like increased incidences of induced labour, instrumental delivery and LSCS with associated morbidities, fetuses are faced with morbidities ranging from IUGR to macrosomia. We here tried to study maternal outcome in post-dated pregnancy. The objective is to study maternal outcome in post-dated pregnancy and to compare maternal outcome in spontaneous versus induced labour in post-dated pregnancy. Methods: This study was done at a tertiary care hospital in obstetrics and gynecology department for duration of 18 months. After screening according to inclusion criteria, all patients who were admitted in labour wards were grouped in two groups according to clinical examination. First group consists of patients with spontaneous onset of labour and second group consists of patients with induction of labour. In each group same protocol for fetal monitoring were performed, and labor monitored according to standard partograph. Maternal outcomes in both groups were studied. Results: Maternal outcomes were nearly same in both groups; induced and spontaneous onset of labour, except rate of LSCS, Which was more in induced group though not statistically significant. Conclusions: Women with uncomplicated post dated pregnancies with good bishop score should be allowed spontaneous labour and those with poor bishop should be offered induction of labour, while women with any complicating factors LSCS should be considered.